Analisis Akuntabilitas Penyaluran Dana Bantuan Sosial pada Pemerintah Provinsi DKI Jakarta - Aulia Azzahra; Ayatulloh Michael Musyaffi; Hera Khairunnisa (Indo Publishing, 2025)
This study analyzes the accountability of social assistance fund distribution by the Provincial Government of DKI Jakarta. The background of this research is the 2023 audit findings from the Audit Board of the Republic of Indonesia (BPK RI), which revealed that social assistance funds were distributed to 5,623 recipients who did not meet the eligibility criteria. The purpose of this study is to understand the practice of accountability and to conduct a SWOT analysis related to accountability in the distribution of social assistance. This research uses a qualitative approach with a case study method. Primary data were collected through interviews with informants from the Social Affairs Office, the Education Office, the Inspectorate of DKI Jakarta Province, and representatives of social assistance beneficiaries. Secondary data were obtained from official documents such as audit reports from BPK RI and relevant regulations. The data were analyzed using Jonathan Koppell’s five dimensions of accountability theory and SWOT analysis. The results of the study show that the practice of accountability in the distribution of social assistance funds by the Provincial Government of DKI Jakarta is in line with the theory of public accountability. However, challenges remain, including data mismatches due to non-real-time updates and suboptimal responses to public complaints. This indicates the need to strengthen integrated data systems, increase public understanding of the importance of updating personal data, and improve coordination among relevant parties to ensure that the assistance is accurately targeted and properly accounted for.